A compliant and biomimetic three-layered vascular graft for small blood vessels. (28th April 2017) - Zhang, Y; Li, X S; Guex, A G; Liu, S S; Müller, E; Malini, R Innocenti; Zhao, H J; Rottmar, M; Maniura-Weber, K; Rossi, R M; Spano, F
Abstract: Engineering a small diameter vascular graft with mechanical and biological properties comparable to living tissues remains challenging. Often, current devices lead to thrombosis and unsatisfactory long-term patency as a result of poor blood compatibility and a mismatch between the mechanical properties of the living tissue and the implanted biomaterial. Addressing all these requirements is essential to produce scaffolds able to survive throughout the life of the patient. For this purpose, we fabricated a novel three-layered vascular graft by combining electrospinning and braiding. Mirroring the structure of human blood vessels, the proposed device is composed of three layers: the intima, the media, and the adventitia. The intima and media layers were obtained by sequentially electrospinning silk fibroin (SF) and poly(L-lactide-co- ε -caprolactone), with ratios selected to match the mechanical properties of the native tissue. For the outer layer, the adventitia, SF yarns were braided on top of the electrospun tubes to create a structure able to withstand high pressures. Compliance, Young's modulus and deformability of the obtained scaffold were similar to that of human blood vessels. Additionally, cytocompatibility of the two layers, media and intima, was assessed in vitro by analysing cell metabolic activity and proliferation of endothelial cells and smooth muscle cells, respectively. Furthermore, heparin functionalization of the scaffolds led to improved anticoagulant properties upon incubation in whole blood. The obtained results indicate a potential application of the herewith designed three-layered construct as a vascular graft for small diameter blood vessel engineering.